Mathematics in historic events - a pedagogical approach for meaning making - O'Connor, Marguerite Miheso (Strathmore University, 2019)
History is written evidence of problem solving strategies that have been used to generate solutions to local and global issues. Historical events are cast in decision that make a memorable impact on humanity. Each historical event is a display of profound mathematization processes that reflect an effective use of resources available at the time of the event. Mathematics has been used by generations to make important decisions some of which have stood the test of time. While History of mathematics focuses on what each culture contributed to the conventional mathematics concepts and theories taught in schools as a subject, Mathematics in a Historic environment is an approach that provides lenses that can be used in identifying mathematical thinking that exists in all historical events. Opportunities for students to enact historical events purposefully focusing on the mathematical reasoning used, illuminates mathematical concepts embedded in the solution process. Using mathematics in historic environment approach introduces meaning making and appreciation of how mathematics has been used for posterity. The approach has the potential to enable learners reflect on historical decisions while contemplating on alternative solutions based on present day available resources for the same problem. This practice affords learners with opportunities for a reflective meaningful conceptualization of mathematics as a living body of knowledge. The pedagogical illustrates the centrality of mathematical thinking in all historical events. This paper shares findings and activities from a study carried out on the effectiveness of this approach for teaching mathematics and seeks an opportunity to discuss the approach as a viable pedagogic strategy that can enhance student engagement with mathematics
Paper presented at the 5th Strathmore International Mathematics Conference (SIMC 2019), 12 - 16 August 2019, Strathmore University, Nairobi, Kenya
Keywords: Mathematics in Historic environment; Problem solving